2012
DOI: 10.1186/2190-4715-24-24
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of genetically engineered crops on pesticide use in the U.S. -- the first sixteen years

Abstract: Background: Genetically engineered, herbicide-resistant and insect-resistant crops have been remarkable commercial successes in the United States. Few independent studies have calculated their impacts on pesticide use per hectare or overall pesticide use, or taken into account the impact of rapidly spreading glyphosate-resistant weeds. A model was developed to quantify by crop and year the impacts of six major transgenic pest-management traits on pesticide use in the U.S. over the 16-year period, 1996-2011: he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
294
1
28

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(341 citation statements)
references
References 36 publications
6
294
1
28
Order By: Relevance
“…The results obtained in this study agree with similar studies in the US, Argentina, and other parts of the world 9,10,35,36 . Data from these studies strongly suggest that the adoption of GM crops increased pesticide use, specifically herbicides sprayed on soybean, as shown by the present study for Brazil.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results obtained in this study agree with similar studies in the US, Argentina, and other parts of the world 9,10,35,36 . Data from these studies strongly suggest that the adoption of GM crops increased pesticide use, specifically herbicides sprayed on soybean, as shown by the present study for Brazil.…”
Section: Resultssupporting
confidence: 83%
“…In the US, Benbrook 10 revealed that between 1996 and 2011, GM crops led to a 183,000-ton increase in pesticides, which is equivalent to 7% of the overall pesticide use for all crops. Between 1995 and 2002, the use of the herbicide glyphosate in soybean production increased from 2,500 to 30,000 tons/year 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural soils are subjected to frequent fertilization with PO 4 -3 and application of glyphosate-based herbicides [45]. The influence of soil P content on glyphosate uptake by plants has been investigated previously [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Seven out of the 10 GM-soy samples we tested surpassed this "extreme level" of glyphosate + AMPA residues, reflecting the increased use of glyphosate on Roundup Ready soybeans in the US (Benbrook 2012). …”
Section: Residues Of Pesticides In the Soymentioning
confidence: 99%